Soft computing and intelligent systems theory and applications - Sinha, N. K. (Naresh Kumar), 1927-; Gupta, Madan M. (San Diego : Academic Press, 2000)
The field of soft computing is emerging from the cutting edge research over the last ten years devoted to fuzzy engineering and genetic algorithms. The subject is being called soft computing and computational intelligence. With acceptance of the research fundamentals in these important areas, the field is expanding into direct applications through engineering and systems science. This book cover the fundamentals of this emerging filed, as well as direct applications and case studies. There is a need for practicing engineers, computer scientists, and system scientists to directly apply "fuzzy" engineering into a wide array of devices and systems.
Soft computing paradigms for artificial vision / K.K. Shukla -- Intelligent control with neural networks / D. Popovic -- Knowledge-based adaptation of neurofuzzy models in predictive control of a heat exchanger / M. Fischer, O. Nelles, and R. Isermann -- Neural network approximation of piecewise continuous functions : application to friction compensation / R.R. Selmic and F.L. Lewis -- Fuzzy adaptive and predictive control of a thermic process / I. Skrjanc and D. Matko -- An intelligent approach to positive target identification / R.-N.P. Singh -- Adaptive agents and artificial life : insights for the power industry / S.A. Harp and T. Samad -- Truck backer-upper control using dynamic neural network / M.M Gupta and D.H. Rao -- Toward intelligent machines : future perspectives / M.M. Gupta and N.K. Sinha.
Includes bibliographical references and index.
Keywords: Soft computing; Expert systems (Computer science).; Computational intelligence; Electronic books